Training surgeon status is not associated with an increased risk of early or late mortality after isolated aortic valve replacement surgery - Saxena, A.; Dinh, D.; Smith, J.; Reid, Christopher; Shardey, G.; Newcomb, A. (Via Medica, 2014)
Background: Few studies have addressed the effect of "trainee surgeon" status on outcomes after isolated aortic valve replacement (AVR). Methods and Results: A retrospective analysis of data, collected by the Australasian Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database Program between June 2001 and December 2009 was performed. Patient demographics, intra-operative characteristics and early morbidity were compared between trainee and staff cases. Multivariate analyses were used to determine the independent association of training status with 30-day and late mortality. Isolated AVR was performed in 2747 patients; of these, 369 (13.4%) were by trainees. Compared to staff cases, trainee cases were less likely to present with renal failure (1.1% vs. 3.7%, p = 0.010) or in a critical preoperative state (1.4% vs. 3.7%, p = 0.020). The mean EuroSCORE was lower in trainee patients, compared to staff patients (8.11 ± 2.80 vs. 8.81 ± 3.09, p < 0.001). Trainee cases had longer mean perfusion (117.9 min vs. 98.9 min, p < 0.001) and cross-clamp (88.8 min vs. 73.2 min, p < 0.001) times. The incidence of early complications was similar between the two groups, except for post-operative myocardial infarction (1.1% vs. 0.3%, p = 0.008) and red blood cell transfusion (43.9 vs. 40.0%, p = 0.006). On multivariate analysis, trainee status was not associated with an increased risk of 30-day mortality (2.2% vs. 2.4%, p = 0.823). Moreover, there was no significant difference in long-term outcomes and 5-year survival was comparable in both groups (89.9% vs. 84.8%, p = 0.274). Conclusions: Isolated AVR can be safely and effectively performed by trainee surgeons who are strictly supervised in the operating theatre especially during the technically complex parts of the procedure. © 2014 Via Medica.